Analysis of information managament in basic health care: A study in Family Health Units - Dos Santos, Beatriz Rosa Pinheiro [UNESP]; Damian, Ieda Pelógia Martins [UNESP] (Universidade Federal da Paraíba, 2019)
Currently, health information systems in the Family Health Units help professionals to produce a high volume of information daily. Given this, it is imperative that this amount of information produced be managed in an intelligent way, with the purpose of facilitating and optimizing the use of information in the daily actions and in the decision-making of these units. The problem that led to the development of this research was: How do Family Health Units use and deal with information management in their work practices and decision making? In view of this, the objective was to analyze the processes of information management and its presence in the work practices of the Family Health Units. The research is qualitative, descriptive and exploratory and applied in the Family Health Units of Gaul, Cândido Mota, Garça and Vera Cruz, municipalities in the state of São Paulo. In order to analyze the data, the Content Analysis method was employed. The analysis showed that the Family Health Units that presented better performance in relation to the primary care indicators showed a more effective performance of some information management practices when compared to the units that presented poor results in relation to the indicators. Therefore, the information management contributes to the results of the practices coming from attending the patients of the units. However, in general, it was possible to perceive that there was no effective information management in the work practices of the analyzed units.
Análise da gestão da informação na atenção básica em saúde: Um estudo em Unidades de Saúde da Família
Keywords: Basic health care; Content analysis; Health information systems; Information management; Patient record